The CADMUS trial - Multi-parametric ultrasound targeted biopsies compared to multi-parametric MRI targeted biopsies in the diagnosis of clinically significant prostate cancer - Grey,A; Scott,R; Charman,S; van,der Meulen J; Frinking,P; Acher,P; Liyanage,S; Madaan,S; Constantinescu,G; Shah,B; Graves,CB; Freeman,A; et al. (Contemporary Clinical Trials, 2017)
OBJECTIVE: To compare the proportion of clinically significant prostate cancers (PCa) found in lesions detected by multiparametric MRI (mpMRI) with that found in lesions detected by multiparametric ultrasound (mpUSS), in men at risk. PATIENTS AND METHODS: CADMUS (Cancer Detection by Multiparametric Ultrasound of the prostate) is a prospective, multi-centre paired cohort diagnostic utility study with built-in randomisation of order of biopsies. The trial is registered ISRCTN38541912. All patients will undergo the index test under evaluation (mpUSS±biopsies), as well as the standard test (mpMRI±biopsies). Eligible men will be those at risk of harbouring prostate cancer usually recommended for prostate biopsy, either for the first time or as a repeat, who have not had any prior treatment for prostate cancer. Men in need of repeat biopsy will include those with prior negative results but ongoing suspicion, and those with an existing prostate cancer diagnosis but a need for accurate risk stratification. Both scans will be reported blind to the results of the other and the order in which the targeted biopsies derived from the two different imaging modalities are taken will be randomized. Comparison will be drawn between biopsy results of lesions detected by mpUSS with those lesions detected by mpMRI. Agreement over position between the two imaging modalities will be studied. DISCUSSION: CADMUS will provide level one evidence on the performance of mpUSS derived targeted biopsies in the identification of clinically significant prostate cancer in comparison to mpMRI targeted biopsies. Recruitment is underway and expected to complete in 2018.